Association of MYBPC3 Gene Polymorphism with Cardiomyopathy Susceptibility in the Jammu Region - Bharti, Shikha; Kumar, Pranay; Kumar, Dharminder; Pathania, Surbhi; Kumar, Parvinder; Banu, Najitha (Journal of Neonatal Surgery, 2025)
Cardiomyopathy is a multifactorial disorder caused by hereditary and environmental factors. The MYBPC3 gene produces cardiac myosin binding protein C (cMyBP-C), which is found in heart (cardiac) muscle cells. This is linked to thick filaments and plays a structural and regulatory role in the contraction of cardiomyocytes. The MYBPC3Δ25bp deletion has been linked to an increased vulnerability to cardiomyopathy. The purpose of this study was to investigate the relationship between the MYBC3 gene polymorphism and the risk of cardiomyopathy in a case-control study from the Jammu region of J&K, UT. Method: A total of 200 subjects were enrolled for the present study, out of which 100 were clinically diagnosed cases of cardiomyopathy and 100 were healthy age matched controls. Genotyping of cases and controls for MYBPC3 polymorphism was done by using Polymerase Chain Reaction (PCR). A statistical analysis was done to ascertain the association of the above said polymorphism with the risk of cardiomyopathy in the population of Jammu region of J&K, UT. Results: The present study revealed the significant association of MYBPC3Δ25bp (rs36212066) gene polymorphism with an increased risk of cardiomyopathy (p=0.03) in our population. The frequency of deletion allele (risk) was found to be higher in cases (10%) than in controls (2%). Further the study indicated that the MYBPC3 Δ25bp allele adds risk for the development of cardiomyopathy in our cases compared to controls [OR (95%CI)- 5.44 (1.16 to 25.52)]. Conclusion: The study found the significant association of MYBPC3 Δ25bp polymorphism with Cardiomyopathy in population of Jammu region.